The Influence of New Students' Motivation in Choosing an Economic Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Sampit - Rodiah, Rodiah; Arnita, Windi Fahmi; soleha, Aisyah Putri; Hadianur, Muhammad (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to determine the motivation of new students in choosing the economics education study program at the teaching and educational sciences faculty, Muhammadiyah University of Sampit. This research is research ex post facto which is research revealing facts based on measuring symptoms that already existed in respondents before this research was conducted. In this research, respondents were determined using the method Purposive Sampling. The respondent criteria used are as: (1) the respondent is a student of the 2024 FKIP UMSA economics follows education study program, (2) the respondent has completed the KRS for semester 1. With this method, 3 respondents were obtained and 1 informant as reinforcement data validity. The data collection technique used was oral interviews. Next, the data is processed by: (a) reducing the data, (b) presenting the data and (c) drawing conclusions. The results of this research show that the motivation of new students in choosing an economics education study program consists of internal and external motivation. Internal motivation is due to intuition/feelings covering 1 person and external motivation is due to broad job prospects as many as 2 people.